Characterisation And Formulation Of Topical Methyl Salicylate Patches: Effect Of Solvents On Adhesion And Drug Permeation - Yeoh, Soo Chin (2023)
Topical methyl salicylate (MS) patch is popular for pain management. The skin permeation profile of MS is important for formulation design but limited studies were conducted. This project aims to investigate the effect of solvents on the characteristics of patches, drug release and permeation of MS. In this project, suitable solvents were first selected for the patch formulation. Attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy was utilised to scan the stratum corneum (SC) sheets treated with solvents and MS. Next, in vitro permeation studies were carried out with 10%v/v of MS in solvents. After that, patches containing 5%w/w of solvents and/or 10%w/w of MS were prepared with Durabond PC 1879A (8%w/w), Nikasol TS-620 (7%w/w), carboxymethyl cellulose (3.5%w/w) and polyvinyl pyrrolidone (3%w/w). Next, the patches formed were subjected to physiochemical characterisation tests, including ATR-FTIR spectroscopy, tackiness test using stainless-steel probe, peel strength test with porcine ear skin, swelling test, in vitro drug release and skin permeation studies. In in vitro permeation studies, MS in propylene glycol (PG) in drug solution displayed the highest skin permeation of MS and followed by Plurol® oleique (PLU), Labrasol® (LA), Transcutol® (TRC), Maisine® (MAI) and isopropyl myristate (IPM) at 24 h.